Composite Paraganglioma of the Celiac Trunk: A Case Report and a Comprehensive Review of the Literature - Tzikos, Georgios; Menni, Alexandra; Cheva, Angeliki; Pliakos, Ioannis; Tsakona, Anastasia; Apostolidis, Stilianos; Iakovou, Ioannis; Michalopoulos, Antonios; Papavramidis, Theodosios (Frontiers in Surgery, 2022)
Introduction: Composite paragangliomas consist of two components, paraganglioma and ganglioneuroma, representing a rare subgroup of paragangliomas. The purpose of the study is to describe a case of composite paraganglioma of the celiac trunk and a brief review of the existing literature. Case Presentation: A 64-year-old female patient with a history of epigastric abdominal pain and a 51mm-diameter tumor found in a Computerized Tomography of the abdomen was admitted to our surgical department for further evaluation and treatment. After a brief preoperative surgical assessment, the patient underwent a mini-laparotomy for the excision of this tumor. After having the results of the pathology report, a comprehensive review of the international literature was carried out by applying the appropriate search terms. Results: As it was found intraoperatively, the tumor was located at the cephalad aspect of the common hepatic artery, over the portal vein and the inferior vena cava. A negative-margin resection was achieved and the tumor was sent for pathology analysis. The final pathology report revealed a composite paraganglioma, with α paraganglioma and a ganglioneuroma component. Seventeen cases of extra-adrenal composite paraganglioma have been reported in the international literature so far. This case was the first one found in the area of the celiac trunk. Conclusions: Composite paragangliomas comprise rare and potentially malignant tumors with variable prognosis. Establishing their diagnosis promptly is of vital significance. Due to the first-described location of the composite paraganglioma in our case, the differential diagnosis of tumors in this area should also include composite paragangliomas.